DESIGN AND FABRICATION OF ADJUSTABLE HANDLE FOR TWO-WHEELER VEHICLE - Harshal Changole; Nikhil Pillai; Sanket Asole; Vaishnavi Chirwatkar; Samrat Kavishwar (EPRA International Journal of Research and Development (IJRD), 2022)
An individual’s fitness is determined by two factors: the cross-section of the muscle fibers recruited to generate force and the intensity of the recruitment. Individuals with a high percentage of type I slow-twitch muscle fibers will be relatively weaker than similar individuals with a high percentage of type II fast-twitch muscle fibers, but will have higher endurance. The genetic inheritance of the muscle fiber type determines the ultimate possible limit of physical strength, although the unique location in this cortex is determined by training. The proportions of individual muscle fibers can be determined by muscle biopsy. Other factors to consider are the ability to recruit muscle fibers for a particular activity, joint angles, and length of each limb. For a given cross-section, shorter limbs can lift more weight. The ability to gain muscle also varies from person to person, mainly depends on the gene that regulates the amount of hormone secreted, but also depends on the person’s gender, age, health and adequate nutrients in the diet. diet. The one-off max test is the most accurate way to determine maximum muscle strength.